Development of an Interactive E-book based on the ARCS Model to Improve Students' Arabic Writing Skills - Wahyuni, Indaha Nur; Sariyatun, Sariyatun; Muchtarom, Moh.; Alhakimi, Hanan (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2025)
Arabic writing skill is the most difficult skill where many students are weak in this skill and the available teaching materials are less engaging. Therefore development of teaching materials based on the ARCS model was needed to help improve students’ motivation and learning outcomes included writing skills. This study is a research and development (R&D) study that aimed to develop an interactive e-book based on the ARCS model on jumlah topic to improve the students’ Arabic writing skills and analyze its feasibility based on the experts’ validation results. This study used an ADDIE model. However, in this article, the discussion only up to the development stage. The subjects are beginner Arabic language learners whom participated in I’dad Awal program of Markaz Arabiyah Course. Data was collected by observation, interview, documentation, and questionnaire techniques to develop the product and analyze its feasibility. The results of this study show that the interactive e-book based on the ARCS model is suitable for use in the learning process, as evidenced by a product validation percentage of 96.67% from subject matter experts, categorized as "highly feasible," and 88.75% from media experts, categorized as "highly feasible" too. The researchers suggest further studies be carried out at the implementation and evaluation stage of the interactive e-book so that the effectiveness of product to improve students’ Arabic writing skills is known. This study can be one of the references and alternative solutions in solving Arabic learning problems, especially in order to improve students’ Arabic writing skills.